THEORETICAL FOUNDATIONS AND INTEGRATION OF ARTIFICIAL INTELLIGENCE (AL) TECHNOLOGIES IN MEDICAL EDUCATION (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
This article examines theoretical foundations and integration mechanisms of artificial intelligence technologies in medical education. The aim is to justify the didactic value of AI tools within competency-based training. The methodology combines system analysis, instructional design, and medical informatics approaches. Scientific novelty lies in adapting AI-driven assessment criteria and clinical reasoning modeling to educational settings while maintaining pedagogical validity and patient-safety-oriented learning outcomes.